ANK3 gene expression in bipolar disorder and schizophrenia. (September 2014) - Wirgenes, Katrine Verena; Tesli, Martin; Inderhaug, Elin; Athanasiu, Lavinia; Agartz, Ingrid; Melle, Ingrid; Hughes, Timothy; Andreassen, Ole Andreas; Djurovic, Srdjan
Summary: ANK3 gene variants have consistently been associated with bipolar spectrum disorder and schizophrenia spectrum disorder. However, the relevance of its encoded protein, ankyrin-3, in these disorders remains elusive. Here, we show that ANK3 gene expression in blood is significantly increased in bipolar disorder and schizophrenia compared with healthy controls. Additionally, we identified potential cis-acting expression quantitative trait loci located close to the transcription start site of one of the isoforms of the gene. These findings suggest that ANK3 mRNA is an interesting marker for further investigation of the underlying mechanisms in psychotic disorders.